Creation of Islamic Brand Equity: A Study of Malaysia - Bukhari, Syeda Nazish Zahra; Bukhari, Syed Asim Ali (International Journal of Islamic Economics and Governance, 2025)
The study explores the relationship between Islamic Branding and Brand Resonance of an Islamic Brand. This study empirically examines the influence of Islamic Branding Antecedents, i.e., Religiosity, Islamic Brand Knowledge, and Islamic Corporate Social Responsibility (ICSR) on Islamic Branding and its subsequent impact on the Islamic Brand Resonance. The research framework is based on the Customer-Based Brand Equity (C.B.B.E) pyramid and the Theory of Self-Congruity. The empirical study is conducted on the Muslim consumers in Malaysia. Survey research was conducted on a sample of 326 Muslim consumers from the cities of Kuala Lumpur, George Town, and Johor Baru. The results reveal a significant influence of Islamic Branding on the Brand Resonance among Muslim consumers in Malaysia. Furthermore, Religiosity, Brand Knowledge, and ICSR positively influence the perceptions of Malaysian Muslim consumers regarding Islamic Branding. Currently, research in the area of Islamic Branding is limited. © 2025 The Author(s). Licensed under CC BY-NC 4.0.